Malignant Melanoma: Diagnostic and Management Update. Issue 2 (August 2018) - Knackstedt, Thomas; Knackstedt, Rebecca W.; Couto, Rafael; Gastman, Brian
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Summarize the changes to the American Joint Committee on Cancer Eighth Edition Melanoma Staging System. 2. List advances in genetic, molecular, and histopathologic melanoma diagnosis and prognostication. 3. Recommend sentinel lymph node biopsy and appropriate surgical margins based on individualized patient needs. 4. Recognize the currently available treatments for in-transit metastasis and advanced melanoma. 5. Describe current and future therapies for melanoma with distant visceral or brain metastases. Summary: Strides in melanoma surveillance, detection, and treatment continue to be made. The American Joint Committee on Cancer Eighth Edition Cancer Staging System has improved risk stratification of patients, introduced new staging categories, and resulted in stage migration of patients with improved outcomes. This review summarizes melanoma advances of the recent years with an emphasis on the surgical advances, including techniques and utility of sentinel node biopsy, controversies in melanoma margin selection, and the survival impact of time-to-treatment metrics. Once a disease manageable only with surgery, a therapeutic paradigm shift has given a more promising outlook to melanoma patients at any stage. Indeed, a myriad of novel, survival-improving immunotherapies have been introduced for metastatic melanoma and more recently in the high-risk adjuvant setting. Abstract : Related Video Content is available Online.